Electrochemistry of copper(II) induced complexes in mycorrhizal maize plant tissues - Zitka, Ondrej; Merlos, Miguel-Angel; Adam, Vojtěch; Ferrol, Nuria; Pohanka, Miroslav; Hubalek, Jaromir; Zehnalek, Josef; Trnkova, Libuse; Kizek, Rene (Journal of hazardous materials, 2012)
Aim of the present paper was to study the electrochemical behavior of copper(II) induced complexes in extracts obtained from mycorrhizal and non-mycorrhizal maize (Zea mays L.) plants grown at two concentrations of copper(II): physiological (31.7 ng/mL) and toxic (317 μg/mL). Protein content was determined in the plant extracts and, after dilution to proper concentration, various concentrations of copper(II) ions (0, 100, 200 and 400 μg/mL) were added and incubated for 1h at 37°C. Further, the extracts were analyzed using flow injection analysis with electrochemical detection. The hydrodynamic voltammogram (HDV), which was obtained for each sample, indicated the complex creation. Steepness of measured dependencies was as follows: control 317 μg/mL of copper<control 31.7 ng/mL of copper<mycorrhizal 31.7 ng/mL of copper<mycorrhizal 317 μg/mL of copper. Based on these results it can be concluded that mycorrhizal fungus actively blocks transport copper(II) ions to upper parts of a plant by means of adsorbing of copper(II) in roots. Rapid complex formation was determined under applied potentials 300, 500 and 600 mV during the measuring HDVs. It was also verified that mycorrhizal colonization reduced root to shoot translocation of Cu(II) ions.
Keywords: Electrochemistry; Copper; koncentrace vodíkových iontů; elektrochemie; kukuřice setá; Hydrogen-Ion Concentration; měď; Flow Injection Analysis; mykorhiza; Mycorrhizae; Symbiosis; symbióza; Zea mays; průtoková injekční analýza